2008
DOI: 10.1002/ptr.2419
|View full text |Cite
|
Sign up to set email alerts
|

Fermented guava leaf extract inhibits LPS‐induced COX‐2 and iNOS expression in Mouse macrophage cells by inhibition of transcription factor NF‐κB

Abstract: The goal of this study was to elucidate the antiinflammatory activities of Psidium guajava L. (guava) leaf. To improve the functionality of guava leaf, it was fermented with Phellinus linteus mycelia, Lactobacillus plantarum and Saccharomyces cerevisiae. The ethanol extract from fermented guava leaf inhibited lipopolysaccharide (LPS)-induced nitric oxide (NO) and prostaglandin E(2) (PGE(2)) production. Western blot analysis showed that fermented guava leaf extract decreased LPS-induced inducible nitric oxide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 21 publications
6
20
0
Order By: Relevance
“…Fermentation can augment the activities of biological substrates by modifying naturally occurring molecules such as isoflavones, saponins, phytosterols, and phenols. The fermented products of plant materials such as the guava leaf have been found to exert antiinflammatory effects by inhibiting inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2), which is mediated via the down-regulation of the NF-jb pathway (Choi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Fermentation can augment the activities of biological substrates by modifying naturally occurring molecules such as isoflavones, saponins, phytosterols, and phenols. The fermented products of plant materials such as the guava leaf have been found to exert antiinflammatory effects by inhibiting inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2), which is mediated via the down-regulation of the NF-jb pathway (Choi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated anti-bacterial (Goncalves et al 2008), anti-diarrheic (Lozoya et al 2002), anti-hyperglycemic (Deguchi and Miyazaki 2010), anti-acne (Qadan et al 2005), and sedative (Steinhaus et al 2009) effects, as well as anti-cough (Jaiarj et al 1999) and narcotic-like (Lutterodt and Maleque 1988) activities of the plant. Recently, guava leaf extracts have been reported to exhibit anti-inflammatory effect by inhibition of transcription factor NF-κB in LPS-stimulated RAW264.7 cells (Choi et al 2008). Also, our studies have been shown to suppress the proliferation of prostate tumor cells through the suppression of AKT/mTOR/S6K1 and MAPKs signaling pathways (Ryu et al 2012) and MMP-2 and MMP-9 expression and activity through the suppression of the ERK1/2 MAPK signaling pathway (Im et al 2012).…”
Section: Introductionmentioning
confidence: 80%
“…This data indicate the OM is a potential candidate as an anti-inflammatory agent because the excessive amounts of NO produced by iNOS mediates both acute and chronic inflammation (Szabo 1995). And aqueous extract of Psidium guajava leaves can provide specific protection from oxidative injury and to some extent on tissue damage (Tandon et al 2012) and fermented guava leaf extract is involved in the inhibition of iNOS and COX-2 via the down-regulation of NF-κB pathway (Choi et al 2008). Also, All orange juices tested showed an evident antioxidant effect (Rapisarda et al 1999).…”
Section: Discussionmentioning
confidence: 97%
“…It also inhibited lipopolysaccharide induced NF-kβ activation. [49] Blocking NF-kβ is a potential strategy for preventing inflammatory bone resorption in treating periodontal disease. [50] Guava due to its anti-inflammatory action, ability to inhibit iNOS, COX-2, NF-kβ could be a valuable agent in treating periodontal disease.…”
Section: Therapeutic Applications In Treating Periodontal Diseasementioning
confidence: 99%